2011
DOI: 10.1002/jssc.201100312
|View full text |Cite
|
Sign up to set email alerts
|

Combined solid‐phase extraction and gas chromatography–mass spectrometry used for determination of chloropropanols in water

Abstract: A sensitive and rapid derivatization method for the simultaneous determination of 1,3-dichloro-2-propanol (1,3-DCP) and 3-chloropropane-1,2-diol (3-MCPD) in water samples has been developed. The aim was to research the optimal conditions of the derivatization process for two selected reagents. A central composite design was used to determine the influence of derivatization time, derivatization temperature and reagent volume. A global desirability function was applied for multi-response optimization. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
(41 reference statements)
2
16
0
Order By: Relevance
“…The results showed that 20% MTBE was optimal for the extraction of 3‐MCPD and its esters from the oil. These results were consistent with previous findings that concentrations of ethyl acetate and MTBE played an important role in the extraction of 3‐MCPD and its esters from oil and fat‐based matrices . It indicates that it is necessary to take into account the polarity of organic solvents involved in the dilution and transesterification of lipophilic 3‐MCPD esters and hydrophilic 3‐MCPD.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that 20% MTBE was optimal for the extraction of 3‐MCPD and its esters from the oil. These results were consistent with previous findings that concentrations of ethyl acetate and MTBE played an important role in the extraction of 3‐MCPD and its esters from oil and fat‐based matrices . It indicates that it is necessary to take into account the polarity of organic solvents involved in the dilution and transesterification of lipophilic 3‐MCPD esters and hydrophilic 3‐MCPD.…”
Section: Resultssupporting
confidence: 92%
“…The results showed that 20% MTBE was optimal for the extraction of 3-MCPD and its esters from the oil. These results were consistent with previous findings that concentrations of ethyl acetate and MTBE played an important role in the extraction of 3-MCPD and its esters from oil and fat-based matrices [22,31,32]. It indicates that it is…”
Section: Effects Of Different Solvents On the Recovery Of 3-mcpd And supporting
confidence: 93%
“…The detection limit was 0.04 mg/kg. Gonzalez and others () combined solid‐phase extraction with GC‐MS to compare the efficiency of the derivatizing activities of BSTFA and HFBI. It was found that the LOD for BSTFA is 1.12 × 10 −2 mg/kg, which is low enough to quantify 3‐MCPD according to the EU.…”
Section: Methods Of Detection—advantages and Disadvantagesmentioning
confidence: 99%
“…An increased implementation of Doehlert uniform shell designs in GC-MS has been observed in the last decade for developing efficient sample treatment methods by monitoring different analytical functions such as recovery [49][50][51][52][53][54][55], analytical signal [56][57][58][59][60][61] and reaction yield [51,62]. Table 4 also shows that regardless of the potential benefits of uniform shell designs, they have not gained widespread popularity among researchers for optimizing systematically and simultaneously GC-MS instrumental variables.…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 98%